2016
DOI: 10.1038/ncomms12623
|View full text |Cite
|
Sign up to set email alerts
|

Graft-infiltrating host dendritic cells play a key role in organ transplant rejection

Abstract: Successful engraftment of organ transplants has traditionally relied on preventing the activation of recipient (host) T cells. Once T-cell activation has occurred, however, stalling the rejection process becomes increasingly difficult, leading to graft failure. Here we demonstrate that graft-infiltrating, recipient (host) dendritic cells (DCs) play a key role in driving the rejection of transplanted organs by activated (effector) T cells. We show that donor DCs that accompany heart or kidney grafts are rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 47 publications
3
104
0
3
Order By: Relevance
“…Only T cells activated by mono-DCs that were generated in response to allogeneic non-self caused graft rejection (5). Furthermore, mono-DCs that accumulated in the graft directly contributed to rejection by propagating the local effector T cell response (7). Other studies have shown that macrophages also respond to allogeneic non-self.…”
Section: Introductionmentioning
confidence: 99%
“…Only T cells activated by mono-DCs that were generated in response to allogeneic non-self caused graft rejection (5). Furthermore, mono-DCs that accumulated in the graft directly contributed to rejection by propagating the local effector T cell response (7). Other studies have shown that macrophages also respond to allogeneic non-self.…”
Section: Introductionmentioning
confidence: 99%
“…Recipient cDCs appear critical for presenting processed donor allopeptides in the indirect pathway and intact donor exosomal MHC in the semidirect pathway, although the role for nonhematopoietic fibroblastic stromal cells in capturing donor exosomes has not been explored (50)(51)(52)54). Additionally, after initial T cell priming, recipient DCs derived from circulating monocytes colonize the graft and help capture and represent alloantigens to effector T cells within the graft to maintain rejection (55). Conversely, plasmacytoid DCs can drive tolerance to vascularized solid organs through the expansion of Tregs (56).…”
Section: Antigen-presenting Cells In Solid Organ Transplantationmentioning
confidence: 99%
“…Transplanted organs/tissues are populated by tissue-resident conventional DCs, which trigger activation of alloreactive T cells, directly by themselves or indirectly by transferring donor alloantigen to the recipient’s conventional DCs that reside in the graft-draining lymphoid organs [14, 15]. Monocyte-derived DCs, originated from blood monocytes, participate at a later time point by re-presenting donor alloantigen and promoting expansion of effector T cells inside the allograft [16]. Plasmacytoid DCs have been implicated in transplantation tolerance [17].…”
Section: Recognition Of Allografts: the Basicsmentioning
confidence: 99%
“…Which host cells the DCs derive from and their function in the alloimmune response, however, have remained unclear. Recently, our groups (Morelli & Lakkis) have shown in mouse heart and kidney allografts that the vast majority of host CD11c + DCs that replace donor DCs within few days after transplantation have phenotypic and functional features of monocyte-derived DCs (mono-DC), that they originate from Ly6C lo (non-classical) host monocytes, and that they play a key role in allograft rejection [16, 56]. First, DCs in the allograft extend dendrites into the capillary lumina of renal allografts, capture effector T cells rolling along the endothelium, and mediate their transendothelial migration into the graft in a cognate Ag-dependent fashion [56].…”
Section: Non-self Recognition By Innate Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation